How Should Men be Made? - Jamie Ranger (Technophany)
Paul B. Preciado’s theory of the pharmacopornographic regime provides a radical theoretical analysis of the relationship between gender, technology and capitalism. Firstly, I explicate Preciado’s key concepts and argue that their overarching theoretical project illuminates neoliberal capitalism’s capture and commodification of sexual energies and desire. I contend that contemporary toxic heteronormativity in extreme online communities may be explained as reactionary internalisation/ resistance to this process. I conclude by suggesting Preciado’s theoretical insights gesture toward a progressive and emancipatory pathway for rethinking masculinity.